Strategies Towards Green Building Index (GBI) Platinum Rating Among Developers - Wei, Beh Ser; Zainal, Rozlin; Shareh Musa, Sharifah Meryam; Kasim, Narimah (Research in Management of Technology and Business, 2020)
Green Building Index (GBI) is a rating tool provides an opportunity for developers and building owners in Malaysia to design and construct green, sustainable buildings that can reduce environmental impact from construction. However, the awareness and challenge for the developer to construct green building may influence the developer to get GBI platinum certification. In Malaysia construction industry, GBI standards is perceived as being too expensive for many developers. Out of the total 516 certification projects, only 20 projects get Platinum certification. The awareness is relatively low for the developers to implement suitable green technology to achieve Platinum certification. Their strategies apply to get the certification will affect the result of achievement. The objectives of the research are to explore the awareness of developer on green building projects, to identify the challenges for developer in achieving platinum rating of GBI and last to investigate the strategies of developer towards achieve platinum rating of GBI. The research was implemented by qualitative method which collects the data by interviews with 3 developers who involved green building GBI platinum certificated projects in Kuala Lumpur, Malaysia. After the interview session, qualitative content analysis method was using for this research. Through the data research, it shows that high investment cost implementation initially was one the biggest challenge faced by the developers to achieve Platinum certification. Most of the respondent agreed that hire expertise and adopting useful green technology can be the strategies to achieve GBI platinum certification. In the conclusion, the research help and encourage more developer and give the awareness to develop more GBI platinum certification green building in Malaysia.